Complete Genome Sequence of an Acinetobacter Strain Harboring the NDM-1 Gene - Sun, Yang (American Society for Microbiology, 2013)
The NDM-1 gene is a significant public health concern. Acinetobacter is one of the most prevalent opportunistic pathogens causing recent nosocomial infections with NDM-1, and drug-resistant strains pose serious threats to public health worldwide. Herein, we present the genomic sequence of Acinetobacter calcoaceticus subsp. anitratus XM1570, a multidrug-resistant isolate that carries the bla(NDM-1) gene.